2023
DOI: 10.1093/jpepsy/jsad041
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Psychological Burden in Pediatric Chronic Pain: A Systematic Review and Meta-Analysis of Associations with Caregiver Sociodemographic and Biopsychosocial Variables

Abstract: Objective To investigate, via systematic review and meta-analysis, caregiver sociodemographic and biopsychosocial factors associated with anxiety, depression, posttraumatic stress symptoms, and stress of caregivers in the pediatric chronic pain context. Methods EMBASE, Medline, and PsycINFO databases were searched from their inception to the search date (April 4, 2022). Studies were included if they examined caregivers of you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…In particular, the presence of depression and anxiety in caregivers is often indicative of burnout. Many studies in the literature corroborate this observation [ 23 - 26 ]. Our research also found a positive correlation between burnout, depression, and anxiety (p < 0.05).…”
Section: Discussionmentioning
confidence: 56%
“…In particular, the presence of depression and anxiety in caregivers is often indicative of burnout. Many studies in the literature corroborate this observation [ 23 - 26 ]. Our research also found a positive correlation between burnout, depression, and anxiety (p < 0.05).…”
Section: Discussionmentioning
confidence: 56%